2013
DOI: 10.4236/asm.2013.31006
|View full text |Cite
|
Sign up to set email alerts
|

Aphrodisiac Activity of Aqueous Extract of <i>Phoenix dactylifera</i> Pollen in Male Rats

Abstract: Aim of study: Ancient literature alluded to the use of a number of plants/preparations as sex enhancer. One of such botanicals is Phoenix dactylifera in which the pollen grain has been acclaimed to be used as an aphrodisiac. However, the validity has not been scientifically tested. Dopamine is known to facilitate male sexual function. Therefore, the present study was undertaken to evaluate the effect of aqueous extract of Phoenix dactylifera pollen on the sexual behavior of male rats and to measure of serum Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Although several secondary metabolites were detected in the AEBCR in this study, the available evidence (testosterone‐ and nitric oxide action) has narrowed down on the alkaloids, saponins and flavonoids. Alkaloids, through their estrogenic properties and saponins by their androgen enhancing property, have been reported to enhance the action of nitric oxide and erection, increase testosterone synthesis and its release which consequently promoted sexual motivation, arousability, ease by which ejaculatory reflexes are activated and sexual performance in this study (Abedi et al., ; Pratap & Rajender, ; Yakubu & Akanji, ; Zade et al., ). The ability of the alkaloids and saponins to increase the serum concentrations of testosterone may be a prerequisite to restoring the functionality of the testes from paroxetine toxicity.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Although several secondary metabolites were detected in the AEBCR in this study, the available evidence (testosterone‐ and nitric oxide action) has narrowed down on the alkaloids, saponins and flavonoids. Alkaloids, through their estrogenic properties and saponins by their androgen enhancing property, have been reported to enhance the action of nitric oxide and erection, increase testosterone synthesis and its release which consequently promoted sexual motivation, arousability, ease by which ejaculatory reflexes are activated and sexual performance in this study (Abedi et al., ; Pratap & Rajender, ; Yakubu & Akanji, ; Zade et al., ). The ability of the alkaloids and saponins to increase the serum concentrations of testosterone may be a prerequisite to restoring the functionality of the testes from paroxetine toxicity.…”
Section: Discussionmentioning
confidence: 52%
“…The restorations of various aspects of sexual and testicular function in drug‐induced sexual dysfunction male animals by plant extracts have been attributed to the presence of alkaloids, saponins, steroids and flavonoids (Abedi, Parviz, Karimian, & Rodsari, ; Pratap & Rajender, ; Yakubu & Akanji, ; Zade, Dabhadkar, Thakare, & Pare, ). Although several secondary metabolites were detected in the AEBCR in this study, the available evidence (testosterone‐ and nitric oxide action) has narrowed down on the alkaloids, saponins and flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaloids and saponins revealed in the extracts of F. asperifolia [15] may account for its androgenic potentials. Many studies have demonstrated that alkaloids elevate testicular cholesterol in male testes while saponins stimulate endogenous testosterone levels probably by raising the level of luteinizing hormone or binding to enzymes involved in steroidogenesis [32, 33]. …”
Section: Discussionmentioning
confidence: 99%
“…Serum GOT and GPT in CPA‐treated animals showed elevation in their activities as the synthetic drug treatment develops several toxic effects after a chronic period of administration (Abedi, Parviz, Karimian, & Rodsari, ). In contrast, the administration of lycopene helped to recover the level of toxicity towards the control as antioxidant therapy reduces the stress‐induced toxicity (Tamilselvan, Bharathiraja, Vijayaprakash & Balasubramanian, ).…”
Section: Discussionmentioning
confidence: 99%